2016
DOI: 10.1016/j.pce.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

State of tectonic stress in Shillong Plateau of northeast India

Abstract: Tectonic stress regime in the Shillong plateau, northeast region of India, is examined by stress tensor inversion. Some 97 reliable fault plane solutions are used for stress inversion by the Michael and Gauss methods. Although an overall NNW-SSE compressional stress is observed in the area, the stress regime varies from western part to eastern part of the plateau. The eastern part of the plateau is dominated by NNE-SSW compression and the western part by NNW-SSE compression. The NNW-SSE compression in the west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…A long span of convergence between Indian and Eurasian plates has caused subduction, underthrusting, and extrusion resulting in widespread lithospheric deformation (Molnar et al, 1977;Molnar, 1984;Tapponnier et al, 2001;DeCelles et al, 2002;Nábelek et al, 2009). Recently and in the past, the NE Indian region has experienced a frequent occurrence of moderate to large-size earthquakes due to ongoing active tectonic convergence (Ni and Barazangi, 1984;Pandey et al, 1995;Parvez and Ram, 1997;Kayal, 2008;Baruah et al, 2014Baruah et al, , 2016Le Roux-Mallouf et al, 2020). In response to the collision, the lithospheric part of these three plates experiences horizontal shortening and surface uplift.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A long span of convergence between Indian and Eurasian plates has caused subduction, underthrusting, and extrusion resulting in widespread lithospheric deformation (Molnar et al, 1977;Molnar, 1984;Tapponnier et al, 2001;DeCelles et al, 2002;Nábelek et al, 2009). Recently and in the past, the NE Indian region has experienced a frequent occurrence of moderate to large-size earthquakes due to ongoing active tectonic convergence (Ni and Barazangi, 1984;Pandey et al, 1995;Parvez and Ram, 1997;Kayal, 2008;Baruah et al, 2014Baruah et al, , 2016Le Roux-Mallouf et al, 2020). In response to the collision, the lithospheric part of these three plates experiences horizontal shortening and surface uplift.…”
Section: Introductionmentioning
confidence: 99%
“…IBR is under compression due to oblique subduction of the Indian plate below the Burma plate, where the NE-SW directed stress across the inner and northern arc is switched to the E-W directed stress near the Bengal Basin. Within NE India and SM, Baruah et al (2016) made an investigation on tectonic stress through inversion of the stress tensor. They observed that compressional stress direction changes from NNW-SSE in the western part of the massif to the NNE-SSW direction in its eastern part.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also in agreement with the gradual eastward shifting of the Dikrong River with the abandonment of paleochannels. Baruah et al (2016) used fault plane solutions for stress inversion method to examine the tectonic stress regime in the Shillong Plateau. Their results suggest that the eastern part of the plateau is R Jayangondaperumal et al…”
Section: Archaeological and Geomorphic Studiesmentioning
confidence: 99%
“…Tectonic stress is one of the fundamental datasets in Earth Sciences comparable with topography, gravity, heat flow and others (Sperner et al 2003). Thus, an investigation into the crustal tectonic stresses is a key point in earth geotectonic studies (Hou et al 2006;Lunina and Gladkov 2007;Ju et al 2013aBaruah et al 2013Baruah et al , 2016Naimi-Ghassabian et al 2015). Furthermore, knowledge of the tectonic stress field can be used in the hydrocarbon industry to foresee stability problems and tectonic fractures (Ju et al 2013b(Ju et al , 2014(Ju et al , 2015, and to optimize reservoir management through tectonic modelling (Sperner et al 2003).…”
Section: Introductionmentioning
confidence: 99%